The gut microbiome in psoriasis and psoriatic arthritis. Issue 6 (December 2019) - Myers, Bridget; Brownstone, Nicholas; Reddy, Vidhatha; Chan, Stephanie; Thibodeaux, Quinn; Truong, Alexa; Bhutani, Tina; Chang, Hsin-Wen; Liao, Wilson
Abstract: This review summarizes existing research on the gut microbiome composition and function in psoriasis and psoriatic arthritis, exploring potential roles in disease pathogenesis, progression, and management. A strong relationship between skin, joint, and gastrointestinal inflammation exists, as demonstrated by an increased prevalence of psoriasis, psoriatic arthritis, and inflammatory bowel disease co-occurring together; however, the link between them has not been fully elucidated. Studies analyzing the gut microbiome in psoriasis and psoriatic arthritis reveal a unique pattern of dysbiosis. With regard to the gut microbiome's role in psoriasis and psoriatic arthritis pathogenesis, we discuss several theories including intestinal permeability, altered immune homeostasis, and imbalance of short- and medium-chain fatty acid-producing bacteria. We also discuss how the gut microbiome affects patient risk of psoriatic arthritis and other serious comorbidities, and how fecal microbes could be used clinically as therapeutic targets or markers of disease.